2014
DOI: 10.1371/journal.pone.0093334
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of TAT-14-3-3ε Fusion Protein against Cerebral Ischemia/Reperfusion Injury in Rats

Abstract: Stroke is the major cause of death and disability worldwide, and the thrombolytic therapy currently available was unsatisfactory. 14-3-3ε is a well characterized member of 14-3-3 family, and has been reported to protect neurons against apoptosis in cerebral ischemia. However, it cannot transverse blood brain barrier (BBB) due to its large size. A protein transduction domain (PTD) of HIV TAT protein, is capable of delivering a large variety of proteins into the brain. In this study, we generated a fusion protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 69 publications
(108 reference statements)
0
26
0
Order By: Relevance
“…PTDs have the ability to traverse the plasma membrane and enter cells on their own without the aid of a specific receptor [18,19]. Tat PTD has been extensively studied and demonstrated the ability to transduce into various cells and in various animal models [20][21][22][23]. We also demonstrated the protective effects of PTDs fusion protein against cell death in vitro and in vivo [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…PTDs have the ability to traverse the plasma membrane and enter cells on their own without the aid of a specific receptor [18,19]. Tat PTD has been extensively studied and demonstrated the ability to transduce into various cells and in various animal models [20][21][22][23]. We also demonstrated the protective effects of PTDs fusion protein against cell death in vitro and in vivo [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 78%
“…PTDs are small peptides with the ability to promote the functions of full-length proteins and enter all tissues including various cells and animal brain. Numerous studies have demonstrated the therapeutic potential of using PTD fusion proteins for the treatment of a variety of diseases [18][19][20][21][22][23][24]. After purified Tat-PIM2 protein was confirmed, we determined transduction ability of Tat-PIM2 protein into HT22 hippocampal neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The initial dosage of recombinant proteins was 10 mg/kg according to previous researches 16–18 . Vehicle-treated mice developed severe injuries with infarct volumes; while EM2 significantly reduced the infarct size and improved behavior score (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Engineered proteins, such as the TAT-linked proteins, have been altered with polyethylene glycol (PEG) and functional peptides to increase the delivery efficiency [136]. The HIV TAT peptide, for example, has been linked to therapeutic proteins to allow efficient translocation across the BBB for ischemic stroke therapy [137]. Intravenously infused PEGylated-hemoglobin (PEG-hemoglobin), for example, has been evaluated in stroke and TBI animal models in which several advantages have been observed including increased stability and circulation time of drugs and increased diffusion to target sites [136,138].…”
Section: Challenges With Growth Factor Therapymentioning
confidence: 99%